Analisis Pesan Persuasif Yang Dibangun Oleh Kementerian Kesehatan Melalui Video Cegah, Lawan, Obati Diabetes Di Youtube - Yunita Permatasari; Sophia Bernadette (LP2M, 2020)
Abstract Health messages are important in the field of public health to encourage behavior change. In 2017, through a “Prevent, Treat, Fight Diabetes” Campaign initiated by the Ministry of Health of the Republic of Indonesia, the Government uploaded a digital video public service advertisement through a you tube account with the username of the Ministry of Health's P2PTM Directorate. This research was conducted to understand how the Persuasion Technique used by the Ministry of Health in building messages contained in the communication campaign carried out through the video. The main question in this connection is how the persuasion technique used in the health campaign